The Potential Role of m6A RNA Methylation in the Aging Process and Aging-Associated Diseases - Sun, Jin; Cheng, Bokai; Su, Yongkang; Li, Man; Ma, Shouyuan; Zhang, Yan; Zhang, Anhang; Cai, Shuang; Bao, Qiligeer; Wang, Shuxia; Zhu, Ping (Frontiers in Genetics, 2022)
N6-methyladenosine (m6A) is the most common and conserved internal eukaryotic mRNA modification. m6A modification is a dynamic and reversible post-transcriptional regulatory modification, initiated by methylase and removed by RNA demethylase. m6A-binding proteins recognise the m6A modification to regulate gene expression. Recent studies have shown that altered m6A levels and abnormal regulator expression are crucial in the ageing process and the occurrence of age-related diseases. In this review, we summarise some key findings in the field of m6A modification in the ageing process and age-related diseases, including cell senescence, autophagy, inflammation, oxidative stress, DNA damage, tumours, neurodegenerative diseases, diabetes, and cardiovascular diseases (CVDs). We focused on the biological function and potential molecular mechanisms of m6A RNA methylation in ageing and age-related disease progression. We believe that m6A modification may provide a new target for anti-ageing therapies.